Insights from think-alouds on how multilingual learners engage in translanguaging in a multilingual science assessment - López, Alexis A. (Frontiers in Communication, 2025)
This study aims to explore how multilingual learners utilize their linguistic and semiotic resources to engage in and complete a digital multilingual science assessment. A bilingual science task, accompanied by bilingual accommodations, was designed to allow students to use all their language and semiotic resources to demonstrate their understanding of the different states of matter. I employed a think-aloud method, incorporating both concurrent and retrospective protocols, to guide 15 middle school students in articulating their thoughts during the multilingual science assessment. This approach aimed to uncover how they utilized their linguistic and semiotic resources and the reasoning behind their selection of specific resources. The findings from this study provide insights into the cognitive processes and decision-making strategies of multilingual learners regarding the selection of language and semiotic resources in a multilingual content assessment. Additionally, implications for designing multilingual content assessments are also discussed.